A Complete (k,r)-Cap in PG(3,p) Over Galois Field GF(4) - Kareem, F. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this paper is to construct the (k,r)-caps in the projective 3-space PG(3,p) over Galois field GF(4). We found that the maximum complete (k,2)-cap which is called an ovaloid , exists in PG(3,4) when k = 13. Moreover the maximum (k,3)-caps, (k,4)-caps and (k,5)-caps.